Association of vitamin D and cardiovascular health - Ghimire, Hridaya Bibhu; Adhikari, Chandra Mani (Nepalese Heart Journal, 2018)
Vitamin D insufficiency or deficiency is highly prevalent due to limited sun exposure especially in urban and elderly population. Vitamin D is now increasingly recognized as a hormone responsible for numerous physiologic functions in different cells and tissues of the human body including heart. Vitamin D has been shown to be linked with hypertension, acute coronary syndrome, heart failure, and atrial fibrillation. This review briefly overviews the relationship between vitamin D deficiency, its supplementation and outcome in cardiovascular health. Nepalese Heart Journal 2018; 15(1): 17-21.